The role of the C-terminus of SUR in the differential regulation of beta-cell and cardiac KATP channels by MgADP and metabolism - Vedovato, N; Rorsman, O; Hennis, K; Ashcroft, F; Proks, P (John Wiley & Sons, Inc, 2018)
ATP‐sensitive potassium (KATP) channels couple the metabolic state of a cell to its electrical activity and play important physiological roles in many tissues. In contrast to β‐cell (Kir6.2/SUR1) channels, which open when extracellular glucose levels fall, cardiac (Kir6.2/SUR2A) channels remain closed. It is known this is due to differences in the SUR subunit rather than cell metabolism. As ATP inhibition and MgADP activation are similar for both types of channels, we investigated channel inhibition by MgATP in the presence of 100 μm MgADP immediately after patch excision (when the channel open probability (PO) is near maximal). The results were strikingly different: 100 μm MgADP substantially reduced MgATP inhibition of Kir6.2/SUR1, but had no effect on MgATP inhibition of Kir6.2/SUR2A. Exchanging the final 42 residues of SUR2A with that of SUR1 switched the channel phenotype (and v.v.), and deleting this region abolished Mg‐nucleotide activation. This suggests the C‐terminal 42 residues are important for the ability of MgADP to influence ATP inhibition at Kir6.2. This region was also necessary, although, not sufficient for activation of the KATP channel in the intact cells by metabolic inhibition (azide). We conclude that the ability of MgADP to impair ATP inhibition at Kir6.2 accounts, in part, for the differential metabolic sensitivities of β‐cell and cardiac KATP channels.